The hydrogen production through enzymatic route using robust organic electrocatalyst graphite Flake-L.Rubellus - Purnami Purnami; Willy Satrio N; I.N.G. Wardana; Femiana Gapsari; Avita Ayu P.S; Sukarni Sukarni; Indra Mamad G; Tuan Amran T.A; Anwar Johari (Case Studies in Chemical and Environmental Engineering)
This study aims to provide low cost active organic catalyst support. Graphite flake improve L.Rubellus hydrogen concentration from 69896 ppm to 8788 ppm in 7200 seconds electrolysis. The functional group, phase, electroactivity, and morphological characterizations performed to reveal the catalytic mechanism. The characterization unveils the kinetics of the catalyst was depends on the L.Rubellus acidification and morphology. The microstructure bumps, porosity, and graphite flake micro-scaled slits support generates asymmetric microfluidic flow (AMF). Both microstructures cooperatively weaken the water intermolecular bond on the passing saltwater ion cluster. Therefore, the developed electrocatalyst improve the water splitting rate without the involvement of metal.